«МУҢЛЫҚ ЗАРЛЫҚ» ДӘСТАНЫНДАҒЫ СЮЖЕТ ҲӘМ МОТИВЛЕР УҚСАСЛЫҒЫ - Базарбаева, Г. (SCIENCE and SOCIETY, 2023)
The article compares the Karakalpak and Kazakh folk poems "Munglyq Zarlyq". The similarity of plots and motives in two folk epics is analyzed based on the context of the epic.